Pengaruh Financial Literacy dan Karakteristik Individu terhadap Retirement Budget melalui Financial Risk Tolerance - Husna, Faizah Maya; Adrianto, Fajri; Rahim, Rida (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to prove the effect of financial literacy, individual characteristics, financial risk tolerance on the retirement budget of the State Civil Apparatus in the Provincial Government of West Sumatra. In addition, this study aims to prove financial risk tolerance as a moderator of the relationship between financial literacy and retirement budget and moderation of the relationship between individual characteristics and retirement budget in the State Civil Apparatus in the Provincial Government of West Sumatra. Data collection was carried out by distributing questionnaires directly or using a Google form. Based on the results of hypothesis testing, it was found that financial literacy, individual characteristics, and financial risk tolerance had a positive and significant effect on the retirement budget, while individual characteristics as measured by gender and number of dependents did not have a significant effect on the retirement budget. Financial risk tolerance weakens the relationship between financial literacy and retirement budget. financial risk tolerance does not moderate the relationship between individual characteristics and the retirement budget of the State Civil Apparatus.